Three new triterpene saponins from Actinostemma lobatum MAXIM and their cytotoxicity in vitro. (March 2015) - Cao, Jia-qing; Li, Wei; Tang, Yun; Zhang, Xiang-rong; Li, Wei; Zhao, Yu-qing
Graphical abstract: Highlights: Three new triterpene saponins were isolated from Actinostemma lobatum MAXIM. Their structures were identified by the interpretation of spectroscopic data. Their cytotoxic activities were evaluated in four human cancer cell lines. Abstract: Three new triterpene saponins, lobatoside O (1 ), actinostemmoside I (2 ) and actinostemmoside J (3 ), were isolated from the herb of Actinostemma lobatum MAXIM. Their structures were elucidated by means of extensive chemical and spectroscopic methods. In addition, cytotoxic activities toward HCT-116, HT-29, MCF-7 and A549 cell lines were tested by the MTT method.